Dietary supplementation with fermented plant product modulates production performance, egg quality, intestinal mucosal barrier, and cecal microbiota in laying hens - Tian, Yong; Li, Guoqin; Zhang, Shuo; Zeng, Tao; Chen, Li; Tao, Zhengrong; Lu, Lizhi (Frontiers in Microbiology, 2022)
Fermented plant product (FPP) is a kind of functional complex containing probiotics and a variety of bioactive substances, which has multiple physiological functions. However, there is no systematic appraisal of FPP as a feed additive for laying hens. This study was conducted to evaluate the utilization of FPP in laying hens. A total of 120 healthy 34-week-old Xianju layers with similar body weight and egg production were randomly allocated into two dietary treatments with four replicates per treatment and 15 birds per replicate for 8 weeks. The dietary treatments included the basal diet without FPP (CON group) and CON diet supplemented with 500 mg/kg of FPP (FPP group). Compared with the CON group, the egg production and egg mass were significantly increased in the FPP group from 38 to 42 and 34 to 42 weeks of age (P < 0.05). Birds fed with the diet containing 500 mg/kg FPP had higher albumen height (P < 0.01) and Haugh unit (P < 0.05) than those of the controls. FPP supplementation significantly increased the villus height (VH) and crypt depth (CD) in the jejunum of laying hens (P < 0.01), as well as the ratio of VH to CD (P < 0.05). The mRNA expression of tight junctions showed that dietary supplementation with FPP significantly increased the expression levels of Occludin (P < 0.01) and ZO-1 (P < 0.05) in jejunum of hens compared to the control group. In addition, dietary supplementation with FPP influenced cecal microbiota of laying hens, which was characterized by the changes in the microbial community composition, including the increased abundances of Firmicutes, Faecalibacterium, Oscillospira, Clostridium, Ruminococcus, and Coprococcus, along with the decreased abundance of Bacteroidetes, Proteobacteria, Phascolarctobacterium, Odoribacter, Desulfovibrio, and Mucispirillum. Spearman's correlation analysis revealed that bacteria such as Faecalibacterium, Ruminococcus, Coprococcus, and Blautia were significantly and positively correlated with the intestinal barrier markers (P < 0.05), with extremely significant correlations between Ruminococcus and ZO-1, and Coprococcus and Occludin (P < 0.01), whereas Desulfovibrio had a negative correlation with the expression of Occludin (P < 0.05). As it can be concluded, FPP supplementation increased the egg production, egg mass, albumen height, and Haugh unit of laying hens, and improved intestinal health by ameliorating intestinal barrier function, which may be partially attributed to the regulation of cecal microbiota. Our findings suggest that FPP has the potential to be used as a feed additive to promote the performance of layers.